Surface replacement arthroplasty of the proximal interphalangeal and metacarpophalangeal joints: The current state - Harvinder Singh; Joseph J Dias (Indian Journal of Plastic Surgery)
Surface replacement arthroplasty for proximal interphalangeal joint and metacarpophalangeal joints are becoming popular. Low profile, anatomically designed implants limit the amount of bone removed but need preservation of the collateral ligaments. Pyrocarbon and cobalt-chrome stemmed unconstrained implants on ultra-high molecular weight polyethylene are the two commonly available bearing surfaces. The indications for small joint arthroplasty are degenerative, post-traumatic or rheumatoid arthritis. Early results are encouraging, primarily in patient satisfaction and pain relief, but are based on low numbers. The main concerns are progressive loss of range due to implant settling, dislocation, squeaking and poor osteo-integration with the appearance of a radiolucent line at the bone-implant interface. Our experience suggests that metacarpophalangeal joint replacements consistently give good results.